Avaliação do efeito neuroprotetor da Pentoxifilina em modelos de convulsão induzidos por Pilocarpina e Pentilenotetrazol em ratos - Siqueira, Rafaelly Maria Pinheiro (2011)
Epilepsy is considered one of the most important brain diseases in all whole world and its prevalence reaches 5%. Pilocarpine (P400) is a cholinergic agonist which is characterized by its capacity to induce seizures that evolutes to status epilepticus similar to human temporal lobus epilepsy. Pentylenetetrazole is a GABA antagonist that imitates the absence seizures and tonic-clonic seizures in humans. In this study it was evaluated the neuroprotective properties of Pentoxifylline, a xantin, on the seizures induced by P400 (400mg/kg, i.p.) and PTZ (80 mg/Kg, i.p.) in male Wistar rats (180 – 200g) in the presence or absence of PTX (25 and 50 mg/kg) administered orally 1 h before seizures induction. After PTZ80 injection it was observed the presence of tonic-clonic seizures. After P400 injection we observed peripheral cholinergic signals, 1st seizure latency and survival index. It was also determined the levels of amino acids in the frontal cortex, temporal lobus, hippocampus and striatum as well as the levels of amines in the striatum through HPLC associated to electrochemical detection. The glicemic levels were determined during the acute phase of seizures process. The results show that pentoxifylline does not alter the peripheral cholinergic signals, nevertheless it increases the 1st seizure latency at the dose of 25 mg/kg in 18% when compared to P400 and increases the same parameter (151.8% and 273.5%) at the doses of 25 mg/kg and 50 mg/kg, respectively, when compared to PTZ80. The survival index increased 32% to both doses when compared to P400 and 36% and 71%, respectively when compared to PTZ80. In the frontal cortex it was observed a significative reduction of glutamate at the groups treated with pentoxifilin. Reduction of 86.4% and 76.2% (25 and 50mg/kg PTX) in relation to P400. The levels of GABA reduced 33.3% and 21.8%. In the temporal cortex reduction of 56.6% and 54.8% on the levels of aspartate PTX (25 and 50mg/kg, respectively). The levels of glutamate reduced 78.2% and 59.2% at the tested doses, respectively. The levels of GABA increased 28% at the dose of 50 mg/kg. On the hippocampus aspartate increased 199.6% at the dose of 25 mg/kg. The levels of GABA increased 511% and 180.9% PTX (25 e 50mg/Kg, respectively). In the striatum glutamate reduced with both tested doses 74.3% and 79.4%. GABA reduced 65.6% and 74%. In the striatum dopamine increased 416.5% at the dose of 25 mg/kg. The levels of DOPAC reduced 48% at the same dose. Serotonin increased 229.5%. All amino acids and amines were quantified in the model of pilocarpine induced seizures. It was observed a markedly increase at the glicemic levels at the groups P400 when compared to Normal group and PTX pretreated groups which have by the way kept glicemic levels similar to normal rats. In conclusion we showed that pentoxifilin significantly increases the 1st seizure latency at both tested models. Pentoxifylline neuroprotection may be related to reduction on the levels of excitatory amino acids and increase in the levels of inhibitory amino acids at different parts of the brain involved in the start, propagation and maintenance of epilepsy. Keeping the glicemic levels similar to the normal could be involved in the neuroprotection induced by pentoxifylline.